Risk of type 2 diabetes mellitus and cardiovascular complications in KCNJ11, HHEX and SLC30A8 genetic polymorphisms carriers: A case-control study. Issue 11 (November 2021) - Aka, Tutun Das; Saha, Urmi; Shati, Sayara Akter; Aziz, Md. Abdul; Begum, Mobashera; Hussain, Md. Saddam; Millat, Md. Shalahuddin; Uddin, Mohammad Sarowar; Islam, Mohammad Safiqul
Abstract: Background: Type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD) are two deadly diseases caused by the complex interaction of multiple genetic loci, lifestyle and environmental factors. Genome-wide association studies described hundreds of susceptibility loci for T2DM and T2DM-related CVD, but it remains uncertain due to geographic and ethnic variations. The objective of this study was to evaluate the associations of KCNJ11 rs5219, SLC30A8 rs13266634 and HHEX rs1111875 polymorphisms with T2DM and related CVD. Methods: Genotyping of all three polymorphisms was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method on 250 T2DM cases and 246 healthy controls. Both descriptive and inferential statistical methods were applied using MedCalc and IBM SPSS software programs for statistical analyses. Results: A significantly increased association of KCNJ11 rs5219 ( p <0.05) with T2DM was found in dominant, recessive, heterozygote, homozygote, and allele model (aOR = 2.23, 2.03, 1.90, 3.09, and 1.80, respectively). For SLC30A8 rs13266634, only dominant, heterozygote, and allele model (aOR = 3.37, 3.59, and 1.79, respectively) showed significantly increased association with T2DM. SNP rs1111875 ( HHEX ) also revealed 2.08, 4.18, 5.93, and 2.08-times significant association in dominant, recessive, homozygote, and allele models. Besides, a significantly reduced correlation of KCNJ11 rs5219 was found with T2DM-related CVD in the recessive and allele model (aOR = 0.40 and 0.65, respectively). Again, a significant difference was observed between T2DM-related CVD and non-CVD patients in terms of gender distribution, fasting blood glucose (FBG), systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol (TC), and triglycerides (TG). Conclusions: Our investigation indicates that KCNJ11 rs5219, SLC30A8 rs13266634 and HHEX rs1111875 polymorphisms are associated with T2DM. Moreover, KCNJ11 rs5219 polymorphism is correlated with the risk of T2DM-related CVD. Abstract : Type 2 diabetes mellitus; Cardiovascular disease; KCNJ11 ; HHEX ; SLC30A8 ; Polymorphism.